Framework for Using BigchainDB in Software Application - Rustemi, Avni; Atanasovski, Vladimir; Risteski, Aleksandar (My University, 2022)
Recently, cryptocurrencies have become very important, as people are investing a lot of money in them, and people slowly are entering in virtual world where physical money is getting lost and all trade is being done with cryptocurrencies which we neither see nor touch, respectively they don’t exist in the form of money as we are accustomed to. Cryptocurrencies are numerous and their values change day by day depending on the interest of people investing in them. In this paper we will present some of the most used cryptocurrencies and their purchase, the energy that these cryptocurrencies consume during the execution of transactions, taking as an example Ethereum. It will be given our models of how the process of cryptocurrency transactions is executed, taking also as an example Ethereum network, We will talk about the future of cryptocurrencies, architecture and data security etc. Our main focus will be on BigchainDB and the possibility of implementing the same by developers, and in particular we will provide a framework on how BigchainDB can be implemented by developers, to create their own software applications and to see in the future the possibility of how the same can be implemented in practice. Our main goal through this paper is to break the taboos of databases that we are used to working with when creating software applications, and introduce as a challenge for us the use of a new database which is less used by developers, but which is more secure, ie. BigchainDB . And the framework that we will present will be as a reference point for researchers on how BigchainDB can be used in their applications.
Keywords: ethereum network, mining, purchase, energy consumption, architecture, data security, BigchainDB, framework.